STUDI LITERATUR TUJUAN IDEAL LEMBAGA KEUANGAN DAN PERBANKAN ISLAM - Andri Soemitra; Awaluddin A; Aqwa Naser Daulay (HUMAN FALAH: Jurnal Studi Ekonomi dan Bisnis Islam, 2021)
Islamic financial and banking institutions are implementation of Islamic economics teachings. Therefore, the goal of Islam must also be the goal realized by Islamic banking and financial institutions. However, in reality, there are many criticisms related to the orientation of Islamic financial institutions and banking objectives which focus more on achieving financial benefits and developing more legalistic financial services but neglect to the objectives as outlined by maqasid al-shariah. This research examines the growing literature studies related to the problems of Islamic financial and banking institutions related to their ideal goal as a form of institutionalization of Islamic values and principles. This study uses a qualitative approach using the Publish and Perish software tool to collect journal articles relevant to the purpose of this study. The contents of the collected articles were analyzed using content analysis and then the data was triangulated to come to a conclusion. The main findings of this study indicate that the objectives of Islamic banking and financial institutions should be to codify maqasid sharia as the ideal goal by taking into account spiritual, social and financial goals.